Diastolic right ventricular filling vortex in normal and volume overload states - Pasipoularides, Ares (Am J Physiol Heart Circ Physiol, 2003)
Functional imaging computational fluid dynamics simulations of right ventricular (RV) inflow fields were obtained by comprehensive software using individual animal-specific dynamic imaging data input from three-dimensional (3-D) real-time echocardiography (RT3D) on a CRAY T-90 supercomputer. Chronically instrumented, lightly sedated awake dogs (n = 7) with normal wall motion (NWM) at control and normal or diastolic paradoxical septal motion (PSM) during RV volume overload were investigated. Up to the E-wave peak, instantaneous inflow streamlines extended from the tricuspid orifice to the RV endocardial surface in an expanding fanlike pattern. During the descending limb of the E-wave, large-scale (macroscopic or global) vortical motions ensued within the filling RV chamber. Both at control and during RV volume overload (with or without PSM), blood streams rolled up from regions near the walls toward the base. The extent and strength of the ring vortex surrounding the main stream were reduced with chamber dilatation. A hypothesis is proposed for a facilitatory role of the diastolic vortex for ventricular filling. The filling vortex supports filling by shunting inflow kinetic energy, which would otherwise contribute to an inflow-impeding convective pressure rise between inflow orifice and the large endocardial surface of the expanding chamber, into the rotational kinetic energy of the vortical motion that is destined to be dissipated as heat. The basic information presented should improve application and interpretation of noninvasive (Doppler color flow mapping, velocity-encoded cine magnetic resonance imaging, etc.) diastolic diagnostic studies and lead to improved understanding and recognition of subtle, flow-associated abnormalities in ventricular dilatation and remodeling.